Social Dynamics of Campus Life Among Non-Muslim Students at Teuku Umar University, Meulaboh, Aceh - Kumalasari, Reni; Mirza Adia Nova; Muhammad Faisal; Baihaqi, Baihaqi (Abrahamic Religions: Jurnal Studi Agama-Agama, 2025)
This study aims to explore the dynamics of campus life for non-Muslim students at Teuku Umar University (UTU). This study focuses on two main aspects, namely the challenges faced by non-Muslim students and the support available from the institution. This research uses a qualitative research method with a phenomenological approach, which aims to understand and describe the phenomena experienced by the research subjects. The data collection techniques used were in-depth interviews. The main informants are non-Muslim students who are studying and employees in the academic department and student affairs at UTU. The findings of this study identify that non-Muslim students at UTU face various challenges. The challenges faced in social interaction are differences in social and cultural norms, limitations in access and facilities for worship, and the existence of negative stigma. In social integration, non-Muslim students face challenges in the process of adjusting to the academic environment. Related to the difficulties faced by non-Muslim students, the campus strives to provide support in the form of providing services in the religious aspect, access and equality, holding inclusive social activities, and support from the academic community. It is hoped that the results of this research can be used as study material to create a responsive and inclusive campus.